2018
DOI: 10.2147/ijgm.s150676
|View full text |Cite
|
Sign up to set email alerts
|

Determining 30-day readmission risk for heart failure patients: the Readmission After Heart Failure scale

Abstract: BackgroundChronic heart failure (CHF), which affects >5 million Americans, accounts for >1 million hospitalizations annually. As a part of the Hospital Readmission Reduction Program, the Affordable Care Act requires that the Centers for Medicare and Medicaid Services reduce payments to hospitals with excess readmissions. This study sought to develop a scale that reliably predicts readmission rates among patients with CHF.MethodsThe State Inpatient Database (2006–2011) was utilized, and discharge data including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 25 publications
6
45
1
1
Order By: Relevance
“…According to the present study, the highest rate of readmission was found in 123 male cases (69.43%). In 2018, Ronald Chamberlain et al reported more readmissions in men (15). In a 2014 study by Jeremiah Brown et al, The mean age of patients discharged for acute myocardial infarction was 78.4 with 51.6% male, which is consistent with this study (16).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…According to the present study, the highest rate of readmission was found in 123 male cases (69.43%). In 2018, Ronald Chamberlain et al reported more readmissions in men (15). In a 2014 study by Jeremiah Brown et al, The mean age of patients discharged for acute myocardial infarction was 78.4 with 51.6% male, which is consistent with this study (16).…”
Section: Discussionsupporting
confidence: 82%
“…Establishing balance between cost of effectiveness and providing high quality care to patients is a constant challenge for modern health care systems (5). In general, hospital readmission is defined as a hospital admission for a specified period of time (7,15,30,60, 90 days or even up to one year), after the initial admission and discharge (6,7). However, the most common time for readmission is 30 days after discharge (7).…”
Section: Introductionmentioning
confidence: 99%
“…We compared the reason for hospitalization at their Liver Cirrhosis-Related Readmissions in USA Gastroenterol Res. 2020;13(1): [11][12][13][14][15][16][17][18] index hospitalization to the reason for hospitalization during their subsequent visit (Table 4). Ascites and hepatic encephalopathy were the two most common reasons for hospitalization leading to readmissions.…”
Section: Resultsmentioning
confidence: 99%
“…Liver Cirrhosis-Related Readmissions in USA Gastroenterol Res. 2020;13(1): [11][12][13][14][15][16][17][18] Efforts have been made to identify the risk factors for readmissions related to other diseases like congestive heart failure (CHF) [11]. Various evidence-based interventions targeting those at risk for CHF-related readmissions have been implemented to attain success in reducing the burden of readmission [12].…”
Section: Introductionmentioning
confidence: 99%
“…Using the previously reported 30‐day readmission rate of heart failure patients of 9%‐30% (Medicare risk standardized rate 23%) and assuming readmission rates for patients with dilated IVC at discharge to be arbitrarily at >50%, the sample size needed to detect this difference in our study would range from 76 to 116 using a standard statistical sample size calculation (power 80%, alpha error rate 0.05). However, if we looked for a smaller effect size in which we are to assume that US guided inpatient HF management would reduce admissions by half to a third, we would need to enroll 116‐580 patients in the study (power 80%, alpha error 0.05).…”
Section: Methodsmentioning
confidence: 99%